Rescue of Targeted Regions of Mammalian Chromosomes by in Vivo Recombination in Yeast - Kouprina, Natalya; Kawamoto, Kensaku; Barrett, J. Carl; Larionov, Vladimir; Koi, Minoru (Genome Research, 1998)
In contrast to other animal cell lines, the chicken pre-B cell lymphoma line, DT40, exhibits a high level of homologous recombination, which can be exploited to generate site-specific alterations in defined target genes or regions. In addition, the ability to generate human/chicken monochromosomal hybrids in the DT40 cell line opens a way for specific targeting of human genes. Here we describe a new strategy for direct isolation of a human chromosomal region that is based on targeting of the chromosome with a vector containing a yeast selectable marker, centromere, and an ARS element. This procedure allows rescue of the targeted region by transfection of total genomic DNA into yeast spheroplasts. Selection for the yeast marker results in isolation of chromosome sequences in the form of large circular yeast artificial chromosomes (YACs) up to 170 kb in size containing the targeted region. These YACs are generated by homologous recombination in yeast between common repeated sequences in the targeted chromosomal fragment. Alternatively, the targeted region can be rescued as a linear YACs when a YAC fragmentation vector is included in the yeast transformation mixture. Because the entire isolation procedure of the chromosomal region, once a target insertion is obtained, can be accomplished in ∼1 week, the new method greatly expands the utility of the homologous recombinationproficient DT40 chicken cell system.